2020
DOI: 10.25134/erjee.v8i2.2987
|View full text |Cite
|
Sign up to set email alerts
|

Applying Digital Storytelling to Improve Indonesian High School Students� Visual Memory and Writing Skill

Abstract: This study investigated the use of digital storytelling in improving students� visual memory and writing skill of tenth grade students in one of senior high school in Tangerang, Indonesia. A total of 72 students are taken as the sample in the current study. The randomized pretest - posttest control group design was used in the study. Using quasi experimental research-non-equivalent control group design, the students in the experimental groups completed the process through digital storytelling. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
(31 reference statements)
2
6
0
1
Order By: Relevance
“…From this point of view, it is demonstrated by both evaluation scores and interviews that students' writing skills have improved. This indicates that digital storytelling is an effective method that can be used to improve writing skills and other research in this field is also consistent with the findings of this research (Aktaş, 2019;Baki, 2015;Baki and Feyzioğlu, 2017;Castillo-Cuesta et al, 2021;Chuang et al, 2013;Çıralı, 2014;Dayan, 2017;Demir ve Kılıçkıran, 2018;Fitri, Husnawadi and Harianingsih, 2021;Foley, 2013;Gider, 2019;Girmen, Özkanal and Dayan, 2019;Gürsoy, 2021;Haşlaman, 2017;Özüdoğru and Çakır, 2020;Riani, Husnawadi and Syarifudin, 2021;Rong and Noor, 2019;Santiana et al, 2021;Saunders, 2014;Sudarmaji, Mulyana and Karsiyah, 2020;Tanrıkulu, 2020;Tarigan and Liana, 2018;Xin, 2013;Yamaç, 2015;Yamaç and Ulusoy, 2016;Yılmaz et al, 2017).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…From this point of view, it is demonstrated by both evaluation scores and interviews that students' writing skills have improved. This indicates that digital storytelling is an effective method that can be used to improve writing skills and other research in this field is also consistent with the findings of this research (Aktaş, 2019;Baki, 2015;Baki and Feyzioğlu, 2017;Castillo-Cuesta et al, 2021;Chuang et al, 2013;Çıralı, 2014;Dayan, 2017;Demir ve Kılıçkıran, 2018;Fitri, Husnawadi and Harianingsih, 2021;Foley, 2013;Gider, 2019;Girmen, Özkanal and Dayan, 2019;Gürsoy, 2021;Haşlaman, 2017;Özüdoğru and Çakır, 2020;Riani, Husnawadi and Syarifudin, 2021;Rong and Noor, 2019;Santiana et al, 2021;Saunders, 2014;Sudarmaji, Mulyana and Karsiyah, 2020;Tanrıkulu, 2020;Tarigan and Liana, 2018;Xin, 2013;Yamaç, 2015;Yamaç and Ulusoy, 2016;Yılmaz et al, 2017).…”
Section: Resultssupporting
confidence: 86%
“…The students stated that the writing activities were fun/good; they learned new information thanks to the activities (Castillo-Cuesta et al, 2021;Özüdoğru and Çakır, 2020;Rong and Noor, 2019;Yamaç, 2015); their writing skills improved (Aktaş, 2019;Baki, 2015;Baki and Feyzioğlu, 2017;Castillo-Cuesta et al, 2021;Chuang et al, 2013;Çıralı, 2014;Dayan, 2017;Demir ve Kılıçkıran, 2018;Fitri, Husnawadi and Harianingsih, 2021;Foley, 2013;Gider, 2019;Girmen, Özkanal and Dayan, 2019;Gürsoy, 2021;Haşlaman, 2017;Özüdoğru and Çakır, 2020;Riani, Husnawadi ve Syarifudin, 2021;Rong and Noor, 2019;Santiana et al, 2021;Saunders, 2014;Sudarmaji, Mulyana and Karsiyah, 2020;Tanrıkulu, 2020;Tarigan and Liana, 2018;Xin, 2013;Yamaç, 2015;Yamaç and Ulusoy, 2016;Yılmaz et al, 2017); it made them like writing (Van Gils, 2005); they increased their interest in writing; they developed their imagination and that they liked the activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the third result of the study, studies using the digital storytelling method in language education have concluded that this method positively affects students' achievement in language and affective factors related to language skills and that it plays an important role in teaching vocabulary. Sudarmaji, Mulyana, and Karsiyah (2020) examined the effect of the digital storytelling method and traditional method on writing success; however, they did not find a significant difference between these two methods, nor did Çiftçi (2019) who determined the effect of digital stories on primary school students' reading skills. Although no significant difference was found between the two studies, the relevant literature shows that using digital storytelling in language education is an effective method in achieving the goals set.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…When students write their own scripts, record their own voices, mix with different types of multimedia, and present their stories to the audience, they interact with the language and use the target language in authentic ways, fostering meaningful learning (Kajder, 2006;Rance-Roney, 2008). Various studies in the literature present the use of DS for the development of such language skills as Writing (Balaman, 2018;Sepp & Bandi-Rao, 2015;Sudarmaji & Mulyana, 2020;Tanrıkulu, 2020) Reading (Anggeraini & Afifah, 2017;Rahimi & Yadollahi, 2017;Yoon, 2013), Listening (Cigerci & Gultekin, 2017;Loniza, Aslina, & Mazlina, 2018;Tahriri, Tous, & MovahedFar, 2015), and Speaking (Baghdasaryan, 2012;Wei, Siriyothin, & Lian, 2018;Yang, Chen, & Hung, 2020). Baghdasaryan (2012) examined the use of DS as homework for developing learners' speaking skills and revealing their attitude towards the program applied in a mixed-method research and concluded that DS provided significant gains in learners' oral production and learners developed positive attitude towards DS use as homework.…”
Section: Studies On the Use Of Digital Storytelling In Language Learningmentioning
confidence: 99%